ANALISIS TEORI PENAWARAN ISLAMI DALAM PRAKTIK UMKM: STUDI KASUS GEPREK BU IDA DI KEDIRI - Moch. Agus Shofawi Mubaroq Agus Shofawi (Institut Agama Islam K.H. Sufyan Tsauri, 2025)
The research aims to analyze the implementation of Islamic Supply Theory within an MSME in Kediri, specifically Warung Geprek Bu Ida. Supply theory from an Islamic economic perspective emphasizes the principles of justice (al−′adl), social responsibility, and environmental sustainability, which serve as the foundation for production activities and pricing. The research employed a field study with a qualitative descriptive approach. Data sources were obtained through direct observation and interviews with the business owner. The study concludes that the Islamic Supply Theory is effectively implemented by the informal MSME Warung Geprek Bu Ida. Its implementation is based on three ethical dimensions: justice (al−′adl) and Maslahah in pricing (by maintaining small margins); informal Social Responsibility (R) in the form of affordable prices as a community contribution; and the internalization of External Costs through Khilafah (stewardship) awareness in waste management. Overall, this case study demonstrates that spiritual motivation (Falah) is the key variable shaping the Islamic supply curve at the micro-business level.